Investigation of plasma turbulence and local electric field in the T-10 tokamak and TJ-II stellarator by HIBP diagnoatic(review) - Krupnik, L.I.; Melnikov, A.V.; Hidalgo, C.; Chmyga, A.A.; Eliseev, L.G.; Ascasibar, E.; Estrada, T.; Komarov, A.D.; Kozachek, A.S.; Liniers, M.; Lysenko, S.E.; Mavrin, V.A.; et al. (Вопросы атомной науки и техники, 2011)
TJ-II stellarator by HIBP diagnostics has been performed. The following similar features of potential were found: the scale of several hundred Volts; the negative sign for densities ne>1×10¹⁹ m⁻³ and comparable values in spite of the different heating methods. When ne or tE rises, the potential evolves to negative values. During ECR heating and associated Te rise, tE degrades and the potential evolves to positive direction. Oscillations of potential and density in the range of Geodesic Acoustic Modes in T-10 and Alfvén Eigenmodes in TJ-II were observed. На токамаці Т-10 і стелараторі TJ-II за допомогою пучка важких іонів в порівняних режимах досліджувалася поведінка потенціалу та його флуктуацій. Виявлені спільні властивості потенціалу: масштаб близько сотен вольт;негативний знак при щільності ne>1×10¹⁹ m⁻³ і порівнянні значення, незважаючи на різні методи нагріву. Коли n_е або t_Е зростають, потенціал зростае у негативну область. При ЕЦР-нагріві і відповідному рості Te, t_Е погіршується, і потенціал змінюється у позитивний бік. Спостерігається коливання потенціалу в діапазоні геодезичних акустичних мод у Т-10 та альфвеновських власних мод у TJ-II На токамаке Т-10 и стеллараторе TJ-II с помощью пучка тяжелых ионов в сравнимых режимах исследовалось поведение потенциала и его флуктуаций. Обнаружены общие свойства потенциала: масштаб порядка сотен вольт; отрицательный знак при плотностях n_е>1×10¹⁹ m⁻³ и сравнимые значения, несмотря на разные методы нагрева. Когда n_е или t_Е растут, потенциал растет в отрицательную область. При ЭЦР-нагреве и соответствующем росте Te, t_Е ухудшается, и потенциал меняется в положительную сторону. Наблюдались колебания потенциала в диапазоне геодезических акустических мод в Т-10 и альфвеновских собственных мод в TJ-II